Edukasi Ergonomi dan Simulasi P3K sebagai Upaya Pencegahan Kecelakaan Kerja pada Nelayan, Desa Kampung Beru, Kab.Takalar - Yulianah Rahmadani; Nurul Mawaddah Syafitri; Fatmawati Hamid (Pusat Riset dan Inovasi Nasional, 2025)
The fishing profession carries a high risk of occupational accidents due to hazardous working environments, limited safety knowledge, and poor ergonomic practices. This community service activity aimed to raise awareness and improve the skills of fishermen in Kampung Beru Village, Takalar Regency, through ergonomic education and first aid simulations. The methods included lectures and hands-on simulations involving 43 participants, covering ergonomic working postures, cardiopulmonary resuscitation (CPR) techniques, and emergency response steps for drowning victims. The results showed increased participant understanding of the importance of ergonomic positions and appropriate emergency actions during drowning incidents. This activity made a positive contribution to improving fishermen's preparedness in preventing and managing workplace accidents, particularly in the traditional fishing sector.